The Impact of Corporate Reputation on the Cost of Equity as Mediated by Earnings Quality - Ana Mardiana (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2021)
A good corporate reputation is essential for a company because it can create value and an intangible asset that makes it difficult for competitors to replicate. This study investigates the effect of company reputation on the cost of equity through earnings quality as an intervening variable. The Corporate Image Index measures the reputation of the company in this study. The cost of equity is measured using the Ohlson method. Modified Jones measures earnings quality as an intervening variable. The sample used in this study were non-financial companies listed on the Indonesia Stock Exchange and the Corporate Image Index from 2016 to 2018. The sample selection was carried out using the purposive sampling method, with a total sample of 189 companies. This research uses a path analysis method with the help of SPSS version 23 software. The theory used in this research is agency theory. Based on this study's statistical results, the company's reputation does not have a significant effect on earnings quality but has a negative and significant effect on the cost of equity. This study also shows that earnings quality has a negative and significant effect on the cost of equity. In addition, the results of the Sobel test show that earnings quality does not mediate the relationship between company reputation and cost of equity.